A Tardy Ulnar Palsy with an Anomalous Course of Ulnar Nerve - Shah, Harsh R.; Hiremath, Amita; Munshi, Parag; Thatte, Mukund R. (Indian Journal of Plastic Surgery, 2023)
Variations are inherent feature of the intricate brachial plexus. They can be at the level of origin, the course, or the innervation pattern of each peripheral nerve. Knowledge of the various described variations can be worthwhile during the routine hand surgery procedures. We present a case of an elderly patient with anomalous intramuscular course of the ulnar nerve presenting with ulnar neuropathy at the elbow.Level of Evidence: IV.
Keywords: anomalous nerve course; ulnar neuropathy; tardy ulnar palsy; cubital valgus deformity; claw deformity